Conductive Silk‐Based Composites Using Biobased Carbon Materials. Issue 44 (18th September 2019) - López Barreiro, Diego; Martín‐Moldes, Zaira; Yeo, Jingjie; Shen, Sabrina; Hawker, Morgan J.; Martin‐Martinez, Francisco J.; Kaplan, David L.; Buehler, Markus J.
Abstract: There is great interest in developing conductive biomaterials for the manufacturing of sensors or flexible electronics with applications in healthcare, tracking human motion, or in situ strain measurements. These biomaterials aim to overcome the mismatch in mechanical properties at the interface between typical rigid semiconductor sensors and soft, often uneven biological surfaces or tissues for in vivo and ex vivo applications. Here, the use of biobased carbons to fabricate conductive, highly stretchable, flexible, and biocompatible silk‐based composite biomaterials is demonstrated. Biobased carbons are synthesized via hydrothermal processing, an aqueous thermochemical method that converts biomass into a carbonaceous material that can be applied upon activation as conductive filler in composite biomaterials. Experimental synthesis and full‐atomistic molecular dynamics modeling are combined to synthesize and characterize these conductive composite biomaterials, made entirely from renewable sources and with promising applications in fields like biomedicine, energy, and electronics. Abstract : The use of biobased carbons to fabricate conductive, highly stretchable, and biocompatible silk‐based composite biomaterials is demonstrated. Biomass is converted into a carbonaceous material via hydrothermal processing, and subsequently applied upon activation as a conductive filler in silk thin films. These conductive composite biomaterials, made entirely from renewable sources, have promising applications in fields like biomedicine, energy, and electronics.